Research trends between childhood obesity and gut microbiota: a bibliometric analysis (2002–2023) - Wang, Mengping; Zhang, Zhen; Liu, Yuxuan; Jian, Enlin; Ye, Peng; Jiang, Hongjie; Yu, Xiaoping; Cai, Peiling (Frontiers in Microbiology, 2024)
In recent years, the prevalence of childhood obesity has escalated alarmingly, posing significant threats to the physical and mental well-being of children, with an elevated likelihood of persisting into adulthood. Notably, recent investigations have uncovered a profound association between intestinal microbiota, a crucial component of the internal milieu, and childhood obesity. Disturbances in intestinal microbiota and their by-products are now understood to be profoundly intertwined with the evolutionary pathway of childhood obesity. Bibliometric analysis offers a deep understanding of the current research landscape, so we apply it to a review of the emerging trends and patterns between childhood obesity and gut microbiota. We conducted a rigorous and extensive search of the Web of Science (WoS) Core Collection database, spanning the years from 1900 to 2023, to analyze scholarly articles pertaining to childhood obesity and gut microbiota. Utilizing VOSviewer, CiteSpace, the R package "bibliometrix," and the online bibliometric analysis platform (https://bibliometric.com/), we delved into the intricate details of research hotspots, academic collaborations, and emerging trends within this domain. The exhaustive search encompassed the globe, uncovering a cumulative total of 1,384 pertinent studies originating from 429 nations. The results were compelling, revealing a profound influence exerted by the United States and China in this specific field of research. Furthermore, it was observed that the volume of scholarly works pertaining to childhood obesity and gut microbiota is steadily growing year on year. The current hot topics in this field include "abuse", "maltreatment", "adverse childhood experiences", "students", and "food addiction". This comprehensive review offers a meticulous exploration of the evolving trends and emerging research agendas pertaining to childhood obesity and gut microbiota over the past two decades. It strives to equip researchers with a thorough understanding of the key nations, institutions, journals, and potential collaborators in these specialized fields. Additionally, it sheds light on the current frontiers of research and strategic avenues for further exploration, thus serving as an invaluable resource for scholars delving deeper into the intricacies of childhood obesity and the gut microbiome.